Pemanfaatan Teknologi Informasi dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan - Rahma, Dwina Razani Yusifa; Sugiartono, Endro (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2023)
This study plan to complete the effect of Utilization of Information Technology and Internal Control Systems on the Quality of Financial Reports at the Sidoarjo Regional General Hospital. This research is a quantitative research. The data source for do research uses primary data by distributing questionnaires with a Likert scale. Using regression with the help of the SPSS22 application as a statistical tool used to test hypotheses. The results of the analysis prove that, partially, the use of information technology has a significant effect, and the internal control system has a significant effect. Simultaneously the use of information technology and internal control systems has a significant effect on the quality of financial reports.